Ação de impugnação de mandato eletivo: análise constitucional e novas perspectivas - Silva, Daniel Monteiro da (2010)
This study is developed in setting in which the Federal Constitution of 1988 completed 22 years of validity, as well as in general elections (national and state) in country. From this perspective, there are multiple reflections, especially on the constitutional mechanisms of popular sovereignty consolidation, the integrity and legitimacy of elections and democracy itself. It has appeared timely, therefore, to examine the development of ensured instrument of these precepts. Thus, it is approached as an object of research to Action of Impugnation to the Elective Mandate- AIEM, under Art.14, § 10 and § 11 of the Constitution of 1988, considering its constitutional and electoral reasons. It is then aimed to review the second AIEM conceptions of scale, systematic interpretation, preservation of constitutional rights and its effectiveness. Specifically, it is analyzed the Action as to the forms of power that relate to this. then it is examined the democracy principal aspects related to the issue. Without being followed, it is the democratic situation in which it is operated. They are also examined the political rights, especially regarding restraint applied to ineligibility and the possibility of integrating the effects of an impugnatory origin. Following, it has been discussed the formation of an early panorama, consisting of constitutional principles applied to electoral constituencies and eminently procedural principles and, according to which subsidizes the operations of such Action. After that, addressing the Election Law, including its concept, its sources, the Electoral Court and its peculiarities and functions. It is also considered the elective office as to its definition, characteristics and ways of accessing and extinguishing it. Afterwards, the Action of Impugnation is studied from its historical evolution of laws, legal, concept and goals. Expanding on the theme, it s highlighted about their chances of traditional appropriateness (economic power abuse, corruption and fraud) and modern (abuse of economic power intertwined with political) business, including the suggestion of suitability in case of abuse of unique political power. It was also identified the injurious potential demand affecting these illicit to enable the Action. Subsequently, other relevant aspects were explored, such as the legitimacy ad causam, competence, secrecy, procedure, recklessness, bad faith, the purpose of the merits and manageable resources. In the end, it is demonstrated an evolution of AIEM, however, still insufficient to reach full intentions that rise it. It is proposed therefore to re-read the action from news perspectives, based on constitutional and electoral precepts, as well as wider interpretation of the appropriateness of their assumptions of suitability and effects, according to a systematic interpretation, all aimed at the preservation of constitutional rights and their own effectiveness